DAMPAK PKG TERHADAP KINERJA GURU DALAM KEGIATAN BELAJAR MENGAJAR MAN 1 PAMEKASAN - Maulana, Syafrianza; Reza Imtiyazul Fikri; Sekar Arum Mahanani (BASA Journal of Language & Literature, 2024)
This research aims to find out the impact of teacher performance appraisal on teaching and learning activities at MAN 1 PAMEKASAN as well as the general problem formulation, namely the impact of teacher performance appraisal on teaching and learning activities at MAN 1 PAMEKASAN using qualitative descriptive research methods using interactive analysis mode. This research presents results based on observation guides and interviews which show the success of teachers in carrying out teaching and learning activities using appropriate methods and being able to guide students towards the school's vision and mission that has been created. Apart from that, this research also proves that teacher performance assessment can have a positive impact. significant impact on student learning outcomes because teachers will receive evaluation and motivation to develop effective learning methods in the classroom